Poultry Coccidiosis: Design and Interpretation of Vaccine Studies - Soutter, Francesca; Werling, Dirk; Tomley, Fiona M.; Blake, Damer P. (Frontiers in Veterinary Science, 2020)
Eimeria infection impacts upon chicken welfare and economic productivity of the poultry sector. Live coccidiosis vaccines for chickens have been available for almost 70 years, but the requirement to formulate blends of oocysts from multiple Eimeria species makes vaccine production costly and logistically demanding. A multivalent vaccine that does not require chickens for its production and can induce protection against multiple Eimeria species is highly desirable. However, despite the identification and testing of many vaccine candidate antigens, no recombinant coccidiosis vaccine has been developed commercially. Currently, assessment of vaccine efficacy against Eimeria, and the disease coccidiosis, can be done only through in vivo vaccination and challenge experiments but the design of such studies has been highly variable. Lack of a ‘standard’ protocol for assessing vaccine efficacy makes comparative evaluations very difficult, complicating vaccine development and validation. The formulation and schedule of vaccination, the breed of chicken and choice of husbandry system, the species, strain, magnitude and timing of delivery of the parasite challenge, and the parameters used to assess vaccine efficacy all influence the outcomes of experimental trials. In natural Eimeria infection the induction of strong cell mediated immune responses are central to the development of protective immunity against coccidiosis. Antibodies are generally regarded to be of lesser importance. Unfortunately, there are no specific immunological assays that can accurately predict how well a vaccine will protect against coccidiosis (i.e. no ‘correlates of protection’). Thus experimental vaccine studies rely on assessing a variety of post-challenge parameters, including assessment of pathognomonic lesions, measurements of parasite replication such as oocyst output or quantification of Eimeria genomes, and/or measurements of productivity such as body weight gain and feed conversion rates. Understanding immune responses to primary and secondary infection can inform on the most appropriate immunological assays. The discovery of new antigens for different Eimeria species and the development of new methods of vaccine antigen delivery necessitates a more considered approach to assessment of novel vaccines with robust, repeatable study design. Careful consideration of performance and welfare factors that are genuinely relevant to chicken producers and vaccine manufacturers is essential.